A Soldier in the Psychoanalytic Army: Claud Daly's 'Defence of the Garrison'. Issue 1 (January 2016) - Singh, Akshi
Abstract : This article discusses the published psychoanalytical writing and unpublished diaries of Claud Dangar Daly. An officer in the colonial army, Daly was posted in India and served in the First World War, which is when he was introduced to psychoanalysis through shell-shock treatment with Ernest Jones. He went on to have two further analyses with Freud, and one with Ferenczi. Daly's diaries are records of his dreams and his interpretations of them, written while Daly was posted in the North Western Frontier of British India. The article explores Daly's relationship to psychoanalysis, politics and his accounts of sexuality through his published and unpublished writings, and uses this to reflect on Freud's insights on groups, civilization and ethics.